2021
DOI: 10.3390/su132112255
|View full text |Cite
|
Sign up to set email alerts
|

Small-Scale Sport Events as Place Branding Platforms: A Content Analysis of Osona’s Projected Destination Image through Event-Related Pictures on Instagram

Abstract: Over the last few decades, various regions have taken advantage of sport as a tool for place branding. One of the most used strategies has been sporting events, which can help to position the regions and improve their image. With regard to destination image (DI), the penetration and popularity of social media such as Instagram has opened new avenues for place promotion and has turned the users of these platforms into active agents in the promotion of DI. This study aims to explore whether the participants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 113 publications
(177 reference statements)
1
2
0
1
Order By: Relevance
“…Through these actions, managers can better understand the desires, motivations and perceptions of the community and visitors, taking into account that image works as a predecessor of satisfaction and loyalty to the event or destination, thus having a considerable influence on recommendation intentions and return (Liu et al , 2015; Marine-Roig, 2019). This also corroborates the use of sporting events for the promotion and improvement of destination image in communications and social media (Taberner and Juncà, 2021; Yan, 2019).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Through these actions, managers can better understand the desires, motivations and perceptions of the community and visitors, taking into account that image works as a predecessor of satisfaction and loyalty to the event or destination, thus having a considerable influence on recommendation intentions and return (Liu et al , 2015; Marine-Roig, 2019). This also corroborates the use of sporting events for the promotion and improvement of destination image in communications and social media (Taberner and Juncà, 2021; Yan, 2019).…”
Section: Resultssupporting
confidence: 82%
“…The former found significant differences in cognitive and affective aspects, while the latter found that the perceived image contained more sentiment content, with social media being relatively positive. Meanwhile, Taberner and Juncá's (2021) research focused on the use of sporting events as strategies to position regions and improve their image by posting content on Instagram. Yan (2019) conducted a case study that aimed to promote a destination's image through a sporting event.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In mountain biking events, the aim is to promote tourism in the visited area, since the sport plays an important role in the formation of the image of a place [43], organizers consider that the events do indeed promote tourism, as shown by the results obtained in po1 [0.78;0.82], being the opportunity to emphasise the physical aspects of the city [44], in relation to the organisation of the event po2 [0.73;0.80], we can mention that the organisers consider that the various sports events are well organised, so it is important that the sports events sector has guidelines and empirical knowledge about the characteristics of the events that can determine their performance [45].…”
Section: Resultsmentioning
confidence: 99%
“…En ese sentido, la tendencia actual en la organización de eventos e itinerarios de turismo activo complementados por actividades físicas y/o disciplinas deportivas se dirige hacia escenarios en los que se decanta por la limitación en el número de participantes, así como en la gestión y control muy marcado de la huella ecológica que producen (Taberner & Juncà, 2021).…”
Section: Marco Teóricounclassified